2009
DOI: 10.1007/s10665-009-9293-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-wave transverse instability of interfacial gravity–capillary solitary waves in a two-layer potential flow in deep water

Abstract: Interfacial gravity-capillary plane solitary waves, driven by the gravitational force in the presence of interfacial tension in a two-layer deep-water potential flow, bifurcate in the form of wavepackets with a non-zero carrier wavenumber at which the phase speed is minimized. A stability property for the interfacial gravity-capillary plane solitary waves is presented within the framework of the full Euler equations: according to a linear stability analysis based on the perturbation method, such waves are unst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(83 reference statements)
1
2
0
Order By: Relevance
“…As has also been shown in other physical settings where gravity-capillary solitary waves bifurcate below the minimum of the phase speed, there exists a positive initial instability growth rate in the long-wave limit of transversely perturbed waves to the dominant solitary-wave propagation if the total mechanical energy of solitary waves is a decreasing function of the solitary-wave speed [2][3][4][5][6][7][8]. The long-wave transverse instability of gravity-capillary solitary waves is important because it gives a dynamic generation mechanism of so-called gravity-capillary lumps [8][9][10], which denote three-dimensional (3D) fully localized solitary waves arising on the surface of a fluid flow or on the interface between two immiscible fluid-flow layers [8,[11][12][13][14].…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…As has also been shown in other physical settings where gravity-capillary solitary waves bifurcate below the minimum of the phase speed, there exists a positive initial instability growth rate in the long-wave limit of transversely perturbed waves to the dominant solitary-wave propagation if the total mechanical energy of solitary waves is a decreasing function of the solitary-wave speed [2][3][4][5][6][7][8]. The long-wave transverse instability of gravity-capillary solitary waves is important because it gives a dynamic generation mechanism of so-called gravity-capillary lumps [8][9][10], which denote three-dimensional (3D) fully localized solitary waves arising on the surface of a fluid flow or on the interface between two immiscible fluid-flow layers [8,[11][12][13][14].…”
Section: Introductionsupporting
confidence: 62%
“…This explains why some qualitative behaviors of the dynamic properties, such as the long-wave transverse instability of plane gravity-capillary solitary waves, between the Euler equations and other associated weakly nonlinear model equations may be similar even though there are some apparent quantitative discrepancies between them (see[9,10]). As a remark, comparing the expression of R for weakly nonlinear solitary waves, of which amplitudes are O( ), with the one from the full Euler equations[1,7], the horizontal momentum of weakly nonlinear solitary waves, not necessarily of the NLS solitary wavepackets, is estimated by +Ḡ 0 {ηḠ 0 {ζ }} ηḠ 0 {ζ }dξ + O( 3 ). (3.1)…”
mentioning
confidence: 99%
“…In the same physical setting, it was shown that plane gravity-capillary solitary waves are unstable under long-wave disturbances in the transverse direction to the dominant solitary-wave propagation (Kim & Akylas 2007), using a perturbation method that is similar to the one used in the earlier studies by Kataoka & Tsutahara (2004a, 2004b and by Kataoka (2006Kataoka ( , 2008. A similar result in the weakly nonlinear long-wave model equation for interfacial gravity-capillary solitary waves was provided by Kim & Akylas (2006), and the generalized result for interfacial gravity-capillary solitary waves by Kim (2009). The commonly verified transverse instability criterion is consistent with an earlier result by Bridges (2001) for general water-wave problems.…”
mentioning
confidence: 80%